Profession Paths In Medicine And Nursing: Opportunities Beyond The Traditional Characters (Journal of Namibian Studies : History Politics Culture, 2022)
This abstract explores the expanding career opportunities available to individuals with backgrounds in medicine and nursing, beyond the traditional clinical roles. It provides a comprehensive overview of various career paths, including research, education, administration, advanced practice, telemedicine, global health, and specialized fields. By examining these diverse avenues, professionals in medicine and nursing can gain insights into potential areas for growth and impact within the healthcare sector and beyond.